An electrode for an electrochemical sensor based on a flower-like nickel selenide loaded boron and nitrogen co-doped carbon particle and application thereof
Patent Information
- Application Number
- CN202611127170.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-27
AI Technical Summary
[0007]本发明针对现有技术中存在的问题,公开一种基于花状硒化镍负载硼氮共掺杂碳粒的电化学传感器用电极及其应用,充分结合花状硒化镍与硼氮共掺杂碳粒的结构与性能优势,实现二者的性能互补与协同增效,有效解决单一材料存在的问题,提升黄嘌呤电化学检测的灵敏度、选择性与稳定性,适配复杂场景下黄嘌呤的精准快速检测需求
本发明通过花状结构设计与硼氮共掺杂碳粒复合改性,实现了两种材料的性能协同互补:花状多级结构提供了大比表面积与充足的活性位点,暴露了更多黄嘌呤催化反应位点,同时构建了通畅的电子与离子传输通道,加快反应动力学;硼氮共掺杂碳粒均匀负载于硒化镍纳米片表面,一方面构建了连续导电网络,弥补了单一硒化镍导电性不足的缺陷,优化了电子传输效率,另一方面阻隔了纳米片团聚堆叠,稳固了材料结构,提升了电极稳定性;此外,硼氮双杂原子共掺杂调控了碳材料电子结构,引入了大量缺陷活性位点,可与硒化镍协同催化黄嘌呤氧化反应,同时优化了碳粒表面亲水性与吸附选择性,强化了界面浸润效果。相较于单一材料修饰电极,本发明所述电极对黄嘌呤展现出更优异的电催化氧化活性,更宽的检测范围更宽和更低的检测限,可满足临床领域黄嘌呤快速精准检测的需求。
Smart Images

Figure CN122983146A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrochemical sensing electrode material technology, specifically relating to an electrochemical sensor electrode based on flower-shaped nickel selenide loaded with boron and nitrogen co-doped carbon particles and its application. Background Technology
[0002] Xanthine is a key intermediate product of purine metabolism in organisms, widely found in human body fluids, animal and plant tissues, and various foods. Its content is an important indicator for assessing human metabolic health. In clinical medicine, abnormal xanthine metabolism can lead to gout, kidney damage, oxidative stress damage, and other conditions. It can serve as an auxiliary diagnostic marker for various diseases, and accurate detection is of great significance for disease screening and treatment.
[0003] Currently, mainstream methods for xanthine detection include high-performance liquid chromatography (HPLC) and fluorescence spectrophotometry. While these methods offer high accuracy, they suffer from drawbacks such as expensive equipment, complex sample pretreatment, long detection cycles, and the inability to perform rapid on-site detection, making them unsuitable for scenarios like point-of-care clinical testing. Electrochemical sensing technology, with its advantages of simple operation, rapid response, low cost, and real-time detection, has become the core technology for rapid xanthine detection. Furthermore, the structure and properties of the electrode modification materials directly determine the sensor's detection sensitivity, selectivity, and stability.
[0004] Nickel selenide is a high-performance nickel-based transition metal selenide widely used in electrochemical sensing. It possesses excellent conductivity and abundant redox active sites, enabling efficient catalysis of the electrochemical oxidation of xanthine and enhancing the sensing response signal. Compared to conventional bulk and granular nickel selenide, flower-shaped nickel selenide features a three-dimensional, multi-level nanoscale structure formed by the self-assembly of nanosheet units. This significantly increases the material's specific surface area, exposing more active sites and creating unobstructed electrolyte and electron transport channels, reducing interfacial charge transfer resistance and accelerating the xanthine electrocatalytic reaction rate. Furthermore, the unique flower-like structure effectively buffers material volume deformation during electrochemical cycling, preventing structural collapse and improving electrode detection stability. However, single flower-shaped nickel selenide suffers from limited conductivity, easy agglomeration and stacking of nanosheets, and poor interfacial stability. When used alone as a modification material, it exhibits insufficient detection sensitivity and poor repeatability, making it difficult to meet the requirements for high-precision xanthine detection.
[0005] Carbon-based materials possess excellent conductivity, chemical stability, and structural adaptability, making them high-quality composite modification materials for electrochemical sensing. In this invention, boron-nitrogen co-doped carbon particles are uniformly attached to the surface of flower-shaped nickel selenide nanosheets in nanoparticle form, specifically addressing the performance limitations of nickel selenide alone. The boron-nitrogen dual heteroatom co-doping utilizes the electron-deficient nature of boron atoms and the electron-rich nature of nitrogen atoms to create a synergistic effect, regulating the electronic structure of the carbon particles, constructing numerous defective active sites, and endowing the carbon particles with excellent electrocatalytic performance. They can synergistically catalyze the xanthine oxidation reaction with flower-shaped nickel selenide, improving detection efficiency. Simultaneously, the carbon particles attached to the leaf surface can construct a continuous conductive network, optimizing the electron transport rate and solving the problem of insufficient conductivity in nickel selenide; they can also prevent direct contact between nanosheets, effectively inhibiting material aggregation and stacking, and stabilizing the composite structure. In addition, boron-nitrogen co-doping can enhance the hydrophilicity of carbon particle surface, strengthen the wetting effect of electrode electrolyte interface, and facilitate xanthine adsorption and enrichment; at the same time, the formed BC and NC active chemical bonds can optimize the interfacial adsorption selectivity, effectively shield the system from interfering substances, significantly improve the anti-interference ability and accuracy of electrode detection, and realize the complementary and synergistic effect of the two materials.
[0006] In summary, single-material nickel selenide exhibits drawbacks such as poor conductivity and structural stability, while pure carbon materials suffer from insufficient electrocatalytic activity. Sensors based on single materials generally suffer from limitations such as high detection limits and narrow detection ranges, failing to meet the demands for accurate and rapid xanthine detection in complex scenarios. Summary of the Invention
[0007] This invention addresses the problems existing in the prior art by disclosing an electrode for an electrochemical sensor based on flower-shaped nickel selenide loaded with boron and nitrogen co-doped carbon particles and its application. It fully combines the structural and performance advantages of flower-shaped nickel selenide and boron and nitrogen co-doped carbon particles, achieving complementary performance and synergistic effects. This effectively solves the problems associated with single materials, improving the sensitivity, selectivity, and stability of xanthine electrochemical detection, and meeting the needs for accurate and rapid xanthine detection in complex scenarios. The electrochemical sensing electrode of this invention includes a glassy carbon electrode substrate and a NiSe@BNC composite material modified on the surface of the glassy carbon electrode substrate. This composite material is composed of flower-shaped nickel selenide nanosheets and boron and nitrogen co-doped carbon particles. The electrode has a simple and low-cost fabrication process, and exhibits a low detection limit and wide detection range when used for quantitative xanthine detection, meeting the application needs of clinical point-of-care testing and other scenarios.
[0008] To achieve the above-mentioned technical objectives, the technical solution adopted by the present invention is as follows: An electrode for an electrochemical sensor based on flower-shaped nickel selenide loaded with boron and nitrogen co-doped carbon particles includes a glassy carbon electrode substrate and a NiSe@BNC composite material modified on the surface of the glassy carbon electrode substrate; the NiSe@BNC composite material is composed of flower-shaped nickel selenide nanosheets and boron and nitrogen co-doped carbon particles.
[0009] Furthermore, the preparation method of the NiSe@BNC composite material is as follows: (1) Preparation of flower-shaped NiSe microspheres: a. Dissolve nickel source, urea and fluorine source in deionized water at a certain molar ratio and stir to form a homogeneous precursor solution; transfer the precursor solution to a high-pressure reactor lined with polytetrafluoroethylene and carry out hydrothermal reaction at 120℃ for 14 hours; after natural cooling, collect the precipitate by centrifugation, wash it alternately with deionized water and anhydrous ethanol, and dry it under vacuum at 60℃ for 12 hours to obtain Ni(OH)2 microspheres. b. Selenium powder and NaBH4 were dispersed in deionized water and stirred continuously to form a NaHSe precursor solution, which was then ultrasonically dispersed. The above Ni(OH)2 microspheres were dispersed in the NaHSe precursor solution, transferred to a high-pressure reactor, and subjected to a solvothermal reaction at 180°C for 16 hours. After naturally cooling to room temperature, the product was collected by centrifugation, washed alternately with deionized water and anhydrous ethanol, and vacuum dried at 60°C for 12 hours to obtain flower-shaped NiSe microspheres. (2) Preparation of B and N co-doped carbon particles (BNC): Carbon source and boron source were dissolved in deionized water, and nitrogen-containing compound was added dropwise while stirring continuously to form a precursor mixture; the precursor mixture was transferred to a high-pressure reactor lined with polytetrafluoroethylene and subjected to hydrothermal reaction at 180°C for 6 hours; after natural cooling, the product was collected by centrifugation, washed alternately with deionized water and anhydrous ethanol, and dried under vacuum at 60°C for 12 hours; the dried product was placed under a nitrogen atmosphere and heated to 800°C at a heating rate of 5°C / min, and held at that temperature for 2 hours for carbonization treatment; after natural cooling to room temperature, B and N co-doped carbon particles (BNC) were obtained by grinding. (3) Preparation of NiSe@BNC composite material: The flower-shaped NiSe microspheres prepared in step (1) and the BNC prepared in step (2) were dispersed in deionized water and ultrasonically dispersed to form a uniform suspension; the solution was then transferred to a high-pressure reactor lined with polytetrafluoroethylene and subjected to a solvothermal reaction at 130°C for 8 hours; after naturally cooling to room temperature, the mixture was heated to 60°C at 500 rpm under magnetic stirring to completely evaporate the water, and finally vacuum dried at 40°C for 24 hours. The NiSe@BNC composite material was collected after vacuum drying.
[0010] Furthermore, in step (1), the nickel source is NiCl2·6H2O, the fluorine source is NH4F, and the molar ratio of the nickel source to urea and the fluorine source is 1:4:2.
[0011] Furthermore, in step (1), the feeding ratio of selenium powder, NaBH4, Ni(OH)2 microspheres and deionized water is 0.095g:0.113g:100mg:40mL.
[0012] Furthermore, in step (2), the carbon source is citric acid, the boron source is boric acid, and the nitrogen-containing compound is ethylenediamine; the feeding ratio of the carbon source, boron source, deionized water and nitrogen-containing compound is 2g:0.3g:30mL:1.2mL.
[0013] Furthermore, in step (3), the feeding ratio of flower-shaped NiSe microspheres, B and N co-doped carbon particles BNC, and deionized water is 100mg:15mg:20mL.
[0014] A method for preparing an electrode for an electrochemical sensor based on flower-shaped nickel selenide loaded with boron and nitrogen co-doped carbon particles includes the following steps: 200 mg of NiSe@BNC composite material is taken, 200 μL of Nafion perfluorinated resin solution (concentration of 5 wt% is commonly used) is added, then 700 μL of anhydrous ethanol is added, and finally 100 μL of deionized water is added to mix and prepare a suspension. After ultrasonic treatment, 10 μL of the suspension is drop-coated onto the surface of a glassy carbon electrode and air-dried at room temperature to obtain the sensing electrode.
[0015] This application relates to the application of electrochemical sensing electrodes in the quantitative electrochemical detection of xanthine.
[0016] Beneficial effects: This invention achieves synergistic and complementary performance of the two materials through a flower-like structure design and boron-nitrogen co-doped carbon particle composite modification: the flower-like multi-level structure provides a large specific surface area and sufficient active sites, exposing more xanthine catalytic reaction sites, while simultaneously constructing unobstructed electron and ion transport channels to accelerate reaction kinetics; the boron-nitrogen co-doped carbon particles are uniformly loaded on the surface of nickel selenide nanosheets, on the one hand constructing a continuous conductive network, compensating for the insufficient conductivity of nickel selenide alone and optimizing electron transport efficiency, and on the other hand preventing nanosheet aggregation and stacking, stabilizing the material structure and improving electrode stability; in addition, boron-nitrogen dual heteroatom co-doping modulates the electronic structure of the carbon material, introducing a large number of defective active sites, which can synergistically catalyze the xanthine oxidation reaction with nickel selenide, while optimizing the hydrophilicity and adsorption selectivity of the carbon particle surface and enhancing the interface wetting effect. Compared with electrodes modified with a single material, the electrode described in this invention exhibits superior electrocatalytic oxidation activity for xanthine, a wider detection range, and a lower detection limit, meeting the needs of rapid and accurate xanthine detection in clinical fields. Attached Figure Description
[0017] Figure 1The images show the SEM and EDS elemental characterization of materials at each stage of this invention; (a) is a low-magnification SEM image of the nickel-based Ni(OH)2 precursor; (b) is a high-magnification SEM image of the nickel-based Ni(OH)2 precursor; (c) is a low-magnification SEM image of pure flower-shaped NiSe microspheres; (d) is a high-magnification SEM image of pure flower-shaped NiSe microspheres; (e) is a low-magnification SEM image of the NiSe@BNC composite material; (f) is a high-magnification SEM image of the NiSe@BNC composite material; and (g) is an EDS energy dispersive spectroscopy (EDS) spectrum of the NiSe@BNC composite material and the elemental mapping distribution of Ni, Se, C, B, and N. Figure 2 The X-ray photoelectron spectrum of the NiSe@BNC composite material of the present invention is shown below; (a) is the full XPS spectrum; (b) is the high-resolution C1s spectrum; (c) is the high-resolution N1s spectrum; (d) is the high-resolution B1s spectrum; (e) is the high-resolution Se3d spectrum; and (f) is the high-resolution Ni2p spectrum.
[0018] Figure 3 The graph shows the differential pulse voltammetry (DPV) curves of the NiSe@BNC modified electrode of this invention measured in xanthine solutions of different concentrations. Figure 4 This is a linear calibration curve of the oxidation peak response current versus xanthine concentration in this invention. Detailed Implementation
[0019] The technical solution of the present invention will be further described below with reference to specific embodiments, but it is not limited thereto.
[0020] Example 1 1. Preparation of flower-shaped NiSe microspheres 0.475 g NiCl2·6H2O (2 mmol), 0.480 g urea (8 mmol), and 0.148 g NH4F (4 mmol) were dissolved in 35 mL of deionized water and stirred at 500 rpm for 30 minutes under magnetic stirring to form a transparent homogeneous solution. The mixture was transferred to a 50 mL polytetrafluoroethylene-lined reactor and heated to 120°C in a forced-air drying oven for 14 hours. After natural cooling, the light green precipitate was collected by centrifugation at 8000 rpm for 8 minutes, washed three times each with deionized water and anhydrous ethanol, and then dried under vacuum at 60°C for 12 hours to obtain Ni(OH)2 microspheres.
[0021] 0.095 g selenium powder (1.2 mmol) and 0.113 g NaBH4 (3 mmol) were dispersed in 40 mL of deionized water and stirred at 500 rpm for 40 minutes under magnetic stirring to prepare a NaHSe precursor solution. 100 mg of synthesized Ni(OH)2 microspheres were then sonicated at 60 kHz for 30 minutes to fully disperse the microspheres in the selenium source solution. The suspension was sealed in a 50 mL autoclave and reacted at 180°C for 16 hours to complete the anion exchange selenization reaction, yielding flower-like NiSe microspheres self-assembled from ultrathin nanosheets. The molar ratio of Ni to Se was 1:1.2, and excess selenium ensured complete conversion to pure phase NiSe. After cooling to room temperature (25°C), the precipitate was collected by centrifugation at 8000 rpm for 8 minutes. The precipitate was washed three times each with deionized water and anhydrous ethanol, and then vacuum dried at 60°C for 12 hours to obtain the flower-like NiSe microspheres. To obtain a uniform flower-like morphology, Ni 2+ The molar ratio of urea and NH4F is fixed at 1:4:2.
[0022] 2. Preparation of B, N co-doped carbon particles (BNC) 2.0 g of citric acid and 0.3 g of boric acid were dissolved in 30 mL of deionized water and stirred at 500 rpm for 20 minutes with magnetic stirring. Then, 1.2 mL of ethylenediamine was added dropwise to the solution, and stirring continued at 500 rpm for 30 minutes to form a homogeneous precursor mixture. The solution was transferred to a 50 mL polytetrafluoroethylene-lined autoclave and heated at 180°C for 6 hours. After cooling to room temperature, the black precipitate was separated by centrifugation at 8000 rpm for 8 minutes, washed three times successively with deionized water and anhydrous ethanol, and then vacuum dried at 60°C for 12 hours. The dried precursor powder was placed in a ceramic boat and pyrolyzed at 800°C for 2 hours under a high-purity nitrogen atmosphere at a heating rate of 5°C / min. The resulting black powder was thoroughly ground to obtain uniform B, N co-doped carbon nanoparticles. This ratio can achieve uniform doping with fine carbon particles and no obvious agglomeration, making it suitable for NiSe surface modification; excessive boric acid will cause a large amount of free boron oxide impurities, and excessive ethylenediamine will cause carbon sheet agglomeration.
[0023] 3. Preparation of flower-shaped NiSe microspheres loaded with B and N co-doped carbon particles (BNC) 100 mg of prepared flower-shaped NiSe microspheres and 15 mg of BNC nanoparticles were dispersed in 20 mL of deionized water, and then sonicated at 60 kHz for 1 hour to form a homogeneous suspension. The solution was transferred to a 50 mL high-pressure reactor lined with polytetrafluoroethylene and heated at 130°C for 8 hours. After cooling to room temperature, the suspension was heated to 60°C at 500 rpm under magnetic stirring to completely evaporate the water, thereby uniformly anchoring the BNC nanoparticles onto the surface of the NiSe nanosheets. Then, it was vacuum dried at 40°C for 24 hours. After vacuum drying, NiSe@BNC composite powder was collected.
[0024] The morphological evolution and elemental distribution of the prepared materials were systematically characterized using scanning electron microscopy (SEM), and the results are as follows: Figure 1 As shown. Low-magnification SEM image ( Figure 1 a) shows that the nickel-based precursor—Ni(OH)₂ microspheres—are monodisperse microspheres with a particle size between 1–2 μm, exhibiting uniform spherical morphology and good dispersibility. (High-magnification image) Figure 1 b) Further, it is shown that the surface of the microsphere is not completely smooth, but has nanoscale micro-protrusions and attached particles, which can provide reaction sites for subsequent selenization modification and functionalization.
[0025] After the selenization reaction, the morphology of the material undergoes a significant change. Low-magnification image of pure nickel selenide (i.e., NiSe microspheres) Figure 1 c) The material exhibits numerous flower-like microspheres assembled from interconnected two-dimensional nanosheets. It retains the spherical framework of the precursor while simultaneously constructing a layered, open structure. (High magnification image) Figure 1 d) It can be seen that the nanosheets are only tens of nanometers thick, and they cross-link to form a three-dimensional porous network structure. This structure is beneficial for electrolyte wetting and ion transport, while also exposing a large number of electrochemical active sites. After modification with boron-nitrogen co-doped carbon nanoparticles, the resulting NiSe@BNC composite material ( Figure 1 (e, 1f) still maintain the flower-like microsphere morphology, but the surface structure is more complex, rough, and dense. High-magnification images ( Figure 1 f) A layer of amorphous carbon particles was clearly observed uniformly coating the surface of the nanosheets, proving the successful loading of the functional carbon component. This layered composite structure is expected to improve overall conductivity, buffer volume deformation during electrochemical reactions, and thus improve the structural stability of the material. Energy Dispersive X-ray Spectroscopy (EDS) and elemental mapping diagram ( Figure 1 (g) It was confirmed that the composite material simultaneously contains five elements: nickel, selenium, carbon, boron, and nitrogen, and that each element is uniformly distributed within the microspheres, proving the successful construction of the target composite structure. This uniform elemental distribution characteristic helps to further improve the electrochemical sensing performance of the material.
[0026] The surface elemental composition and chemical valence states of the NiSe@BNC composite material were characterized using X-ray photoelectron spectroscopy (XPS). (Full spectrum) Figure 2 a) The clear appearance of characteristic diffraction peaks corresponding to C 1s, N 1s, B 1s, O 1s, Se 3d, and Ni 2p proves that the multi-component NiSe@BNC composite material has been successfully prepared. No impurity characteristic signals were observed in the spectrum, indicating that the sample has high purity and that each target element has been effectively doped into the material system.
[0027] like Figure 2 As shown in b, the high-resolution C1s spectrum can be fitted with multiple characteristic peaks: the main peak at 284.6 eV is attributed to the C–C bond, while characteristic peaks of C–N and C–B bonds are observed at 285.6 eV and 284.1 eV, respectively. This result confirms that boron and nitrogen heteroatoms have been successfully doped into the carbon framework, inducing the formation of numerous defect sites and modulating the local electronic structure of carbon materials. This facilitates charge redistribution and enhances the activity of interfacial electrocatalytic reactions.
[0028] N 1s high-resolution spectrum ( Figure 2 c) The peaks can be fitted to three nitrogen configurations: pyridine nitrogen (398.6 eV), pyrrole nitrogen (401.3 eV), and graphitic nitrogen (405.7 eV). Pyrrole nitrogen is the dominant nitrogen form, indicating that nitrogen atoms are mainly embedded in the non-six-membered ring structure of the carbon matrix. The presence of graphitic nitrogen proves that some nitrogen atoms replace carbon atoms in the graphite carbon network, which can effectively improve the material's conductivity and electron transport rate.
[0029] B 1s spectrum ( Figure 2 d) The peaks can be fitted to two configurations: B–C bond (185.7 eV) and B–C=O bond (187.9 eV), with B–C=O being the predominant form of boron. This indicates that boron atoms were successfully embedded in the carbon lattice, introducing electron-deficient active sites and regulating the surface polarity of the material, thus promoting the adsorption and activation of reaction intermediates.
[0030] Se 3d spectrum ( Figure 2 e) Exhibits a typical spin-orbit splitting double peak: Se 3d 5 / 2 (54.8 eV) and Se 3d 3 / 2 (55.7eV), while a weak Se–O characteristic peak is present at 59.1eV, indicating that the selenium element on the surface of the material has undergone slight oxidation due to air exposure.
[0031] High-resolution Ni 2p spectrum ( Figure 2 f) Ni 2p appears 3 / 2 (856.6 eV) and Ni 2p 1 / 2 The (874.4 eV) spin splitting double peak, accompanied by a distinct satellite oscillation peak, proves that nickel is mainly present in the form of divalent nickel (Ni).2+ The high-intensity satellite peaks further indicate that the 3d orbitals of nickel atoms are not fully filled, reflecting a strong electronic interaction between NiSe and the carbon phase, while also providing a large number of catalytically active nickel sites.
[0032] In summary, the XPS characterization results fully demonstrate that the NiSe@BNC composite material achieves an organic combination of the Ni–Se active phase and the boron-nitrogen co-doped carbon matrix, constructing a multi-valence, multi-element synergistic composite catalytic structure.
[0033] Example 2 Preparation of electrochemical sensing electrodes Before electrode modification, the bare glassy carbon electrode (GCE, 3 mm in diameter) was thoroughly polished with alumina powder until the electrode surface achieved a mirror-like finish. Then, 200 mg of the NiSe@BNC composite material obtained in Example 1 was mixed with 200 μL of Nafion perfluorinated resin solution, followed by 700 μL of anhydrous ethanol and finally 100 μL of deionized water to prepare a suspension. After ultrasonic treatment, 10 μL of the suspension was drop-coated onto the surface of the glassy carbon electrode, ensuring uniform coverage of the electrode substrate. The electrode was then air-dried at room temperature to obtain the sensing electrode. The resulting nickel selenide@boron nitrogen co-doped carbon-modified glassy carbon electrode (denoted as NiSe@BNC / GCE) was air-dried at room temperature until the solvent completely evaporated before use.
[0034] Example 3 Using the NiSe@BNC / GCE glassy carbon modified electrode prepared in Example 2 as the working electrode, a platinum wire electrode as the counter electrode, and an Ag / AgCl electrode as the reference electrode, all three electrodes were simultaneously immersed in 10 mL of 0.1 mol / L phosphate buffer solution (PBS, pH=7.0) and connected to a CHI660F electrochemical workstation via three wires to construct a simple electrochemical sensor. After successful construction of the electrochemical sensor, xanthine standard solutions of different concentration gradients were added dropwise to the phosphate buffer solution, and the DPV curves were measured one by one using the differential pulse voltammetry method built into the electrochemical workstation. The results are as follows: Figure 3 As shown.
[0035] like Figure 3 A clear oxidation peak belonging to the electro-oxidation of xanthine appears at a potential of 0.72V, and the oxidation peak current shows a monotonically increasing trend with increasing xanthine concentration, while the catalytic peak potential shows no significant shift. Figure 4 The linear calibration curves showed an excellent linear relationship between the oxidation peak current (Y) and xanthine concentration (X), with a linear regression equation of Y = 1.22X + 4.78 and a correlation coefficient as high as R0. 2 =0.9992. This sensor has an ultra-wide linear detection range, ranging from 8.21 × 10⁻⁶. -3 ~1.68×102 μM, while the limit of detection (LOD) is as low as 6.2 nM.
[0036] Example 4 Human serum sample spike recovery experiment This study employed standard spiked recovery experiments to verify the practical application performance of the NiSe@BNC electrochemical sensor in real human serum samples. Relevant analytical data are summarized in Table 1. The human serum samples used in the experiment were obtained from the local hospital blood bank, and all subjects signed informed consent forms.
[0037] Test method: Four equal serum samples were taken, and 4 μM, 5 μM, 6 μM, and 7 μM xanthine standards were added to each sample. Each sample was measured in parallel five times. The xanthine concentration was detected by the DPV method, and the spiked recovery rate was calculated. The results are shown in Table 1 below.
[0038] As shown in Table 1, the initial xanthine concentration detected in the blank serum background without added xanthine was 1.48 μM. Spike recovery tests were conducted by adding four different concentrations of xanthine standard solution (4, 5, 6, and 7 μM) to the serum system. Each spiked concentration was measured in parallel (n=5), and the results were taken as the arithmetic mean. The recovery rates for the four spiked levels ranged from 99.5% to 101.4%. This near-100% recovery rate indicates that complex endogenous biomolecules in human serum have almost no interference with the quantitative detection of xanthine, and the NiSe@BNC modified electrode exhibits excellent resistance to matrix interference in real biological fluid systems. These results fully demonstrate that the NiSe@BNC sensor can directly quantify xanthine in real clinical serum samples with high accuracy and reliable results, showing promising prospects for practical application.
[0039] Table 1 Results of xanthine spiked recovery test in human serum It should be noted that the above embodiments are merely some preferred embodiments of the present invention, and not all embodiments. Obviously, based on the above embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of the present invention.
Claims
1. An electrode for an electrochemical sensor based on flower-shaped nickel selenide loaded with boron-nitrogen co-doped carbon particles, characterized in that, The invention includes a glassy carbon electrode substrate and a NiSe@BNC composite material modified on the surface of the glassy carbon electrode substrate; the NiSe@BNC composite material is composed of flower-shaped nickel selenide nanosheets and boron-nitrogen co-doped carbon particles.
2. The electrode for an electrochemical sensor based on flower-shaped nickel selenide-loaded boron-nitrogen co-doped carbon particles according to claim 1, characterized in that, The preparation method of the NiSe@BNC composite material is as follows: (1) Preparation of flower-shaped NiSe microspheres: a. Dissolve the nickel source, urea and fluorine source in deionized water at a certain molar ratio and stir to form a homogeneous precursor solution; The precursor solution was transferred to a high-pressure reactor lined with polytetrafluoroethylene and subjected to hydrothermal reaction at 120°C for 14 hours. After natural cooling, the precipitate was collected by centrifugation, washed alternately with deionized water and anhydrous ethanol, and dried under vacuum at 60°C for 12 hours to obtain Ni(OH)2 microspheres. b. Selenium powder and NaBH4 were dispersed in deionized water and stirred continuously to form a NaHSe precursor solution, which was then ultrasonically dispersed. The above Ni(OH)2 microspheres were dispersed in the NaHSe precursor solution, transferred to a high-pressure reactor, and subjected to a solvothermal reaction at 180°C for 16 hours. After naturally cooling to room temperature, the product was collected by centrifugation, washed alternately with deionized water and anhydrous ethanol, and vacuum dried at 60°C for 12 hours to obtain flower-shaped NiSe microspheres. (2) Preparation of B and N co-doped carbon particles (BNC): Carbon source and boron source were dissolved in deionized water, and nitrogen-containing compound was added dropwise while stirring continuously to form a precursor mixture; the precursor mixture was transferred to a high-pressure reactor lined with polytetrafluoroethylene and subjected to hydrothermal reaction at 180°C for 6 hours; after natural cooling, the product was collected by centrifugation, washed alternately with deionized water and anhydrous ethanol, and vacuum dried at 60°C for 12 hours; the dried product was placed in a tube furnace and heated to 800°C at a heating rate of 5°C / min under a nitrogen atmosphere and held at that temperature for 2 hours for carbonization treatment; after natural cooling to room temperature, B and N co-doped carbon particles (BNC) were obtained by grinding. (3) Preparation of NiSe@BNC composite material: The flower-shaped NiSe microspheres prepared in step (1) and the BNC prepared in step (2) are dispersed in deionized water and ultrasonically dispersed to form a uniform suspension. The solution was then transferred to a high-pressure reactor lined with polytetrafluoroethylene (PTFE) and subjected to a solvothermal reaction at 130°C for 8 hours. After natural cooling to room temperature, it was heated to 60°C at 500 rpm under magnetic stirring to completely evaporate the moisture. Finally, it was vacuum dried at 40°C for 24 hours. The NiSe@BNC composite material was collected after vacuum drying.
3. The electrode for an electrochemical sensor based on flower-shaped nickel selenide-supported boron-nitrogen co-doped carbon particles according to claim 2, characterized in that, The nickel source in step (1) is NiCl2·6H2O, the fluorine source is NH4F, and the molar ratio of the nickel source to urea and the fluorine source is 1:4:
2.
4. The electrode for an electrochemical sensor based on flower-shaped nickel selenide-loaded boron-nitrogen co-doped carbon particles according to claim 2, characterized in that, In step (1), the feeding ratio of selenium powder, NaBH4, Ni(OH)2 microspheres and deionized water is 0.095g:0.113g:100mg:40mL.
5. The electrode for an electrochemical sensor based on flower-shaped nickel selenide-loaded boron-nitrogen co-doped carbon particles according to claim 2, characterized in that, The carbon source in step (2) is citric acid, the boron source is boric acid, and the nitrogen-containing compound is ethylenediamine; the feeding ratio of the carbon source, boron source, deionized water and nitrogen-containing compound is 2g:0.3g:30mL:1.2mL.
6. The electrode for an electrochemical sensor based on flower-shaped nickel selenide-supported boron-nitrogen co-doped carbon particles according to claim 2, characterized in that, Step (3) The feeding ratio of flower-shaped NiSe microspheres, B and N co-doped carbon particles BNC, and deionized water is 100mg:15mg:20mL.
7. A method for preparing an electrode for an electrochemical sensor based on flower-shaped nickel selenide-supported boron-nitrogen co-doped carbon particles as described in any one of claims 1-6, characterized in that, Includes the following steps: The bare glassy carbon electrode is polished to a mirror finish using alumina powder. Take 200 mg of NiSe@BNC composite material, add 200 μL of Nafion perfluorinated resin solution, then add 700 μL of anhydrous ethanol, and finally add 100 μL of deionized water to prepare a suspension. After ultrasonic treatment, take 10 μL of the suspension and drop it onto the surface of the glassy carbon electrode. Air dry at room temperature to obtain the sensing electrode.
8. The application of the electrochemical sensing electrode according to any one of claims 1 to 7 in the quantitative electrochemical detection of xanthine.